A SIMPLE METHOD ON EQUIPMENT SELECTION METHODOLOGY OF VAPOR COMPRESSION REFRIGERANT ELECTRIC VEHICLE AIR-CONDITIONING SYSTEM - Sukri, M.F.; Musa, M.N.; Sumeru, K.; Sodiya, S. (Journal of Advanced Manufacturing Technology (JAMT), 2015)
This paper presents a simple method on equipment selection of vapor compression refrigerant, electric vehicle airconditioning system i.e. electric compressor and electronic expansion valve (EEV). This method utilized validated compartment cooling load model to identify maximum cooling capacity of selected vehicle specifications. The maximum cooling capacity determined the appropriate sizes of the compressor and electronic expansion valve by matching the predicted maximum cooling capacity with data published by the manufacturer. By using this method, the predicted maximum cooling capacity of a 1.6L Proton Wira Aeroback passenger car was estimated at 2.9 kW. The results show that the appropriate electric compressor and EEV for the air-conditioning system are from high voltage brushless DC variable speed hermetic compressor, type SIERRA06-0982Y3 and Danfoss EEV type ETS 6 – 14 respectively.